Seismic Performance of a Three-Story Reinforced Concrete Building with Masonry Infill Walls and Friction Base Support - Pamuda Pudjisuryadi; V.S. Prayogo; S.I. Oetomo; Benjamin Lumantarna (Institute of Research and Community Outreach - Petra Christian University, 2021)
The stiffness of masonry infill walls is commonly neglected in design practice of Reinforced Concrete (RC) structures. In fact, the stiffness of masonry infill wall may significantly influence seismic performance and dynamic behavior of RC buildings. In this research, influence of masonry infill walls to the structural performance of a three-story RC frame is investigated. In addition, possible application of friction-based support is also studied. Full 3D non-linear time history analysis is conducted to observe behavior of the structure under two-directional ground motion. In the analysis, any failed elements are removed subsequently from the model to avoid numerical analysis problem. The result shows that the placement of masonry infill walls can significantly influence the structural behavior of RC structure. Inappropriate placement of masonry wall may lead the building undergo soft-story mechanism. It is also found that the use of friction-based support can effectively improve the seismic performance of the building.